Gestión del proceso de cobranza con respecto de los créditos en la Empresa Asesorlimju S.A. de la ciudad de Babahoyo periodo 2022. - Avilés Villamarin, Danna Yahily (2023)
The process of managing credit collection in the company Asesorlimju S.A. of the city of Babahoyo during the 2022 period presents a critical challenge that requires immediate attention. The importance of addressing the management of the collection process with respect to credits in Asesorlimju S.A. during the 2022 period lies in how critical this area is to the financial health and long-term viability of the company. The objective of this document is to determine the causes that cause the mismatch in the accounts receivable of the company ASESORLIMJU S.A. of the period 2022. The application of a mixed methodology in the present case study on the management of the collection process in ASESORLIMJU S.A. would be highly beneficial. Based on the results of the Current Liquidity Ratio based on the data provided by the company, a worrying situation is observed for ASESORLIMJU S.A. in 2022. With a Current Liquidity Ratio of 0.625, the company presents a clear liquidity deficit. Based on all of the above, it can be concluded that they provide a clear and worrying image of the company's financial situation in 2022. One of the most relevant findings is the evident lack of liquidity, highlighted by both the financial indicators and by internal perceptions.